EFISIENSI ENERGI PRODUKSI BIOGAS AIR LIMBAH PABRIK KELAPA SAWIT PADA SUHU TERMOFILIK - Fiqih Pertiwi; Sarono -; Udin Hasanudin; Tanto Pratondo Utomo (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
Palm oil mill effluent treatment using anaerobic pond system was not effective because it needs large area and causes greenhouse gas emission. Thermophilic anaerobic digestion system can make hydraulic retention time of palm oil mill effluent becomes shorter. The purposes of this research were to determine the optimum temperature, net energy balance of the utilization from palm oil mill effluent at thermophilic temperature, and study the possibility of its application on palm oil mill.  Palm oil mill effluent and sludge characterization were determined by analyzing pH and COD (Chemical Oxygen Demand), then 40 L palm oil mill effluent and 10 L sludge were fermented in the bioreactor stirred at temperature 45oC and 55oC.  The data were presented in tables and graphs then analyzed descriptively. The Results showed that for 50 L palm oil mill effluent at 45oC needed 113,906 J/57 days and produced net energy value 22,078 MJ/57 days, while at 55oC needed 113,934 J/43 days and produced net energy value 23,622 MJ/43 days.  Based on the calculation palm oil mill with capacity of 60 tonnes FFB/hour, will produce electrical energy equivalent to 1,654 MW and produce extra energy value 13.699,32 MJ/hour in the processing of FFB into CPO. Keywords : Energy efficiency, thermophilic anaerobic digestion system